How to Support Faculty as They Prepare to Teach Online - Susan C. Biro (Adult Education Research Conference, 2004)
A survey, an in-depth interview, and a review of the literature were used to explore the changes faculty undergo as they transition a course from traditional into online delivery. It was discovered that group trainings, ongoing individual training, mentoring, and a variety of critical reflective activities best supported this group.